Overseas Education: The Perspective of the Acehnese Scholarship Applicants - Restu Andrian; Teuku Azhari; Nur Akmaliyah; Ika Kana Trisnawati; Muntasir Muntasir (Proceedings of AICS - Social Sciences, 2019)
Students leave their countries to pursue tertiary education abroad under different motives. To understand this case, this study aimed to identify the prospective students’ perceptions on overseas academic settings. A total of 100 Acehnese students applying for overseas scholarship were surveyed. The obtained data were then processed using SPSS 24.0 for descriptive quantitative elaboration. The findings indicated that both females and males shared relatively similar views on the quality of international tertiary education. Both positively consider overseas universities to have better learning quality, better learning environment and better research experience. It is suggested that prospective students equip themselves with good English language competence to increase their chance to study abroad.